Public Policy As An Effort To Prevent Early Marriage Through Parental Participation - Saddam Husein; Henny Nuraeny; Nova Monaya; Ani Yumarni; Hidayat Rumatiga (Jurnal Legisci, 2025)
Background.The high rate of early marriage in Indonesia is influenced by factors such as tradition, social norms, economy, and low parental education levels. Parents often serve as the final decision-makers in child marriages, making their participation crucial in prevention efforts. Aims. This study aims to analyze the effectiveness of public policies in preventing early marriage through approaches that involve active parental participation. Methods. The method used is sociological juridical with a qualitative approach, conducted through discussion forums, coaching, and legal and health education for parents. Conclusion. The results show that the government has issued various policies, such as Law Number 16 of 2019, as well as programs such as BIMWIN, BRUS, marriage clinics, and women’s and children’s empowerment. However, these efforts are not yet optimal without improving parental capacity and awareness. The novelty of this research lies in its emphasis on legal and health education for parents as a strategic step in preventing early marriage. The implication is the need for integrative policy synergy between the government, society, and families